2004
DOI: 10.1111/j.1365-2648.2003.02965.x
|View full text |Cite
|
Sign up to set email alerts
|

Reported pain after day surgery: a critical literature review

Abstract: There is a disparity in reported levels of pain after day surgery. It is important that a unified day surgery pain measurement strategy is established, so that patients can be informed about the intensity of pain that they are likely to experience following specific procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 39 publications
(41 reference statements)
2
43
0
Order By: Relevance
“…As the major goal of patient management in day-case surgery is to promote patient comfort and satisfaction by reducing the anticipated side-effects of surgery and anaesthesia, this finding supports the promotion of patient well-being as a health care outcome [26,27]. Previously, patients have reported pain as the most common side effect of day-case surgery [28,29]. It can be concluded that health professionals have managed to treat pain satisfactorily after day-case surgery in this sample.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…As the major goal of patient management in day-case surgery is to promote patient comfort and satisfaction by reducing the anticipated side-effects of surgery and anaesthesia, this finding supports the promotion of patient well-being as a health care outcome [26,27]. Previously, patients have reported pain as the most common side effect of day-case surgery [28,29]. It can be concluded that health professionals have managed to treat pain satisfactorily after day-case surgery in this sample.…”
Section: Discussionsupporting
confidence: 69%
“…The major goal of patient management in daycase surgery is to promote patient comfort and satisfaction by reducing the anticipated side effects of surgery and anaesthesia. A number of studies concentrate on these side effects and comfort questions [ 26,27], especially pain [28,29] and nausea and vomiting [30]. Safety in day-case surgery operations has also been one of the main interests in these studies [31].…”
Section: Introductionmentioning
confidence: 99%
“…The distance learning programmes presently offered appear so far to have made little impact. Secondly, considerable evidence suggests that pain management following day surgery (28)(29)(30)(31)(32)83) , pre and post-operative psycho-educational intervention (33)(34)(35)(36)(37)84) , nurse-led pre-assessment clinics (38,39,85) and post-operative primary care (40,41,86) remain challenging issues in need of improvement. Exposure to day surgery practices was extremely limited in pre-registration programmes and 90% of Staff Nurses had undertaken no formal education in day surgery since qualification.…”
Section: F U T U R E O F N U R S I N G W I T H I N T H E M O D E R N mentioning
confidence: 99%
“…Many transferable skills will certainly have been acquired during other clinical placements although numerous aspects within modern surgery are unique because of the limited time available on the day of surgery i.e. rapid recovery from anaesthesia (68)(69)(70) , post-operative pain management (31) and early discharge following surgery (68,(71)(72)(73)(74) . Undoubtedly, extensive clinical supervision and clinical mentorship will have also occurred during the period since qualification.…”
Section: L I N I C a L N U R S I N G R O L E Smentioning
confidence: 99%
See 1 more Smart Citation